2020
DOI: 10.1007/s13555-020-00358-y
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Chromoblastomycosis Caused by Fonsecaea pedrosoi Successfully Treated by Oral Itraconazole Together with Terbinafine

Abstract: Patients with chromoblastomycosis (CBM) usually have a history of local skin damage related to outdoor activities, mainly manifested as chronic refractory proliferative pathologic changes. We report a case of a 56-year-old man with CBM, identified as Fonsecaea pedrosoi infection by fungal culture and gene sequencing. This patient was successfully treated with a regimen of oral itraconazole (ITZ) and terbinafine lasting 7 months. Through in vitro drug sensitivity tests, minimum inhibitory concentrations of amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Este fármaco quando administrado por via oral possui efeitos fungistáticos e fungicidas através da inibição da esqualeno-epoxidase, que interfere na biossíntese de ergosterol e função da membrana fúngica (28,29) . Estes fármacos são considerados seguros em casos de tratamento prolongado como CBM (14) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este fármaco quando administrado por via oral possui efeitos fungistáticos e fungicidas através da inibição da esqualeno-epoxidase, que interfere na biossíntese de ergosterol e função da membrana fúngica (28,29) . Estes fármacos são considerados seguros em casos de tratamento prolongado como CBM (14) .…”
Section: Discussionunclassified
“…Cladophialophora carrionii é o patógeno predominante em regiões secas e semidesérticas da Austrália, África do Sul, Venezuela e Cuba, enquanto Fonsecaea pedrosoi é o agente mais comum encontrado em zonas tropicais úmidas, como Amazônia e regiões temperadas da América Latina (13) . Outros fungos dematiáceos têm sido associados com menor frequência a CBM, entre eles temos: Phialophora verrucosa, Rhinocladiella aquaspersa, Exophiala dermatitidis, Exophiala jeanselmei e Exophiala spinifera (14,15) . De acordo com processo fisiopatológico da CBM, a infecção ocorre após traumatismo da pele e inoculação traumática de fungos dematiáceos (16) .…”
Section: Os Agentes Etiológicos Mais Comuns Pertencem Aos Gêneros Cladophialophora Eunclassified
“…Chromoblastomycosis caused by Fonsecaea spp. has been reported in countries including Argentina (Label et al, 2018), Venezuela (Paniz-mondol et al, 2008), Peru (Schwalb & Seas, 2020), China (Bao et al, 2018;You et al, 2019;Zhang et al, 2019;Shen et al, 2020;Chen et al, 2021), India (Varghese et al, 2016), the United States (Takei et al, 2007), Mexico (Carolina et al, 2015), Canada (Mourad & Haber, 2020), and Cuba (Badali et al, 2013). Molecular phylogenetic analyses have shown that several sibling species are involved.…”
Section: Introductionmentioning
confidence: 98%